A Revision of the Genus Argolis (Hemiptera: Reduviidae: Stenopodainae) from Asia - Zhuo Chen; Michael D. Webb; Wanzhi Cai (Insects, 2023)
The assassin bug genus Argolis Stål, 1861 (Hemiptera: Reduviidae: Stenopodainae) has a disjunct distribution in Sub-Saharan Africa and Asia. In the present study, the Asian species of Argolis are revised. Two species are recognized, redescribed, and illustrated, with the following new subjective synonyms and new combination proposed: Argolis Stål, 1861 = Bardesanes Distant, 1909, syn. nov. = Neoklugia Distant, 1919, syn. nov.; A. farinator (Reuter, 1882) = N. typica Distant, 1919, syn. nov. = B. sericenotatus Livingstone & Ravichandran, 1989, syn. nov.; A. signata (Distant, 1909), comb. nov. (transferred from Bardesanes) = Caunus noctulus Hsiao, 1977, syn. nov. Lectotypes for C. farinator, B. signatus, and N. typica are designated. A key to separate the two Asian species of Argolis is provided. The sexual dimorphism, systematic relationships, and distribution of Argolis are discussed. Argolis is newly recorded from Laos, Pakistan, and Vietnam.